Empowering the agenda of the Malay world: the experiences of the International Institute of Malay World and Islamic Civilisation, International Islamic University Malaysia - Zakariya, Hafiz; S., Suryadi (2017)
Although Indonesia and Malaysia are now two independent nations, both countries have a lot in common, tied by a common religion, language and cultural heritage dating back centuries ago. In building a better tomorrow, both nations can benefit from each other’s rich experiences. This presentation will focus on an educational institute established at the International Islamic University (Henceforth, IIUM) in 2016 initially named the Centre for Malay World and Islamic Civilisation and now has been transformed as the International Institute of Malay World and Islamic Civilisation (Henceforth, MALAY WORLD). The institute, which is the brainchild of the Honourable Tan Sri Dato’ Seri Utama Dr. Rais Yatim (Henceforth, Tan Sri Rais), is established to support the efforts of the university in creating an academic and intellectual field of research and studies focusing on the Malay World and Islamic civilization. This paper will describe the scope, major types of activities and concerns of the institute. In so doing it will identify the potential areas for collaboration (such as academic exchange, research, international conference) with relevant institutions in Indonesia. Finally, it will discuss the experiences of this young but ambitious institute in order to share its achievements and challenges in order to obtain response and feedback from audience for the betterment of the Institute and scholars and institutions in both nations.